Policing Predictive Policing - Andrew G. Ferguson (Washington University Law Review, 2017)
Predictive policing is sweeping the nation, promising the holy grail of policing—preventing crime before it happens. The technology has far outpaced any legal or political accountability and has largely escaped academic scrutiny. This article examines predictive policing’s evolution with the goal of providing the first practical and theoretical critique of this new policing strategy. Building on insights from scholars who have addressed the rise of risk assessment throughout the criminal justice system, this article provides an analytical framework to police new predictive technologies.
Keywords: Policing Predictive Policing; Predictive Policing; Actuarial Justice; Criminal justice; Law enforcement; Predictive strategy; Intervention strategies; complex social network analysis; social map; predictive technology